2011
DOI: 10.1016/j.biortech.2011.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Thermophilic co-digestion of organic fraction of municipal solid wastes with FOG wastes from a sewage treatment plant: Reactor performance and microbial community monitoring

Abstract: Working at thermophilic conditions instead of mesophilic, and also the addition of a co-substrate, are both the ways to intend to improve the anaerobic digestion of the source-collected organic fraction of municipal solid wastes (SC-OFMSW). Addition of sewage treatment plant fat, oil and grease wastes (STP-FOGW), that are nowadays sent to landfill, would represent an opportunity to recover a wasted methane potential and, moreover, improve the whole process. In this study, after a first period feeding only SC-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…R. xylanolyticum is a rumen bacterium and degrades xylan. It has been earlier reported in a thermophilic anaerobic reactor co-treating organic fraction of municipal solid wastes and fat, oil and grease wastes [37]. G. thermotolerans grows between 25 and 54 C and at pH 6.0e8.3.…”
Section: Microbial Community Analysismentioning
confidence: 94%
“…R. xylanolyticum is a rumen bacterium and degrades xylan. It has been earlier reported in a thermophilic anaerobic reactor co-treating organic fraction of municipal solid wastes and fat, oil and grease wastes [37]. G. thermotolerans grows between 25 and 54 C and at pH 6.0e8.3.…”
Section: Microbial Community Analysismentioning
confidence: 94%
“…Synergistetes is a group of microorganisms that couples H 2 production to the consumption of volatile fatty acids (Sekiguchi et al, 2000) and it has also been detected in other similar studies (Martin-Gonzalez et al 2011). Many other studies have also found members of the Firmicutes and the Bacteroidetes to be very abundant in different anaerobic reactors (Zhang et al 2011;Martin-Gonzalez et al 2011;Calderon et al 2011).…”
Section: Analysis Of the Domain Bacteriamentioning
confidence: 89%
“…Many other studies have also found members of the Firmicutes and the Bacteroidetes to be very abundant in different anaerobic reactors (Zhang et al 2011;Martin-Gonzalez et al 2011;Calderon et al 2011). Firmicutes are known for being very resistant microorganisms, as well as endospore producers.…”
Section: Analysis Of the Domain Bacteriamentioning
confidence: 95%
“…In addition, stable digestions were obtained at substrate concentration of 100 g/L for sludge digestion and 101.5 g/L for co-digestion. It was reported that thermophilic digestion has some advantages over mesophilic digestion, including higher digestion rate, greater conversion of organics to biogas, as well as destruction of pathogenic microorganisms [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%